INTERNALISASI NILAI KEIKHLASAN DAN PENGORBANAN DALAM KHUTBAH IDUL ADHA SEBAGAI PENDEKATAN BIMBINGAN KONSELING ISLAMI MELALUI KEGIATAN BERBASIS EKSPRESI SOSIAL DI MASJID AL JAMI’UL HADI KABUPATEN PADANG PARIAMAN - Desep Pria Pandri; Vera Sriwahyuningsih; Ridho Rismi (STKIP Subang, 2026)
Eid al-Adha is a spiritual occasion rich in Islamic educational values, particularly the virtues of sincerity and sacrifice exemplified by Prophet Ibrahim (AS) and Prophet Ismail (AS). These values ​​hold significant relevance for the character development of both individuals and the community. This study aims to analyze the internalization of the values ​​of sincerity and sacrifice conveyed through Eid al-Adha sermons as an approach to Islamic guidance and counseling, utilizing social expression-based activities at Al Jami’ul Hadi Mosque in Padang Pariaman Regency. The research employs a mixed-methods approach (quantitative and qualitative), utilizing observation, interviews, documentation, and questionnaires distributed to the congregation participating in Eid al-Adha activities. The study subjects comprised 50 individuals, including mosque administrators, the *qurban* (sacrificial) committee, mosque youth members, and the general public. The results indicate that Eid al-Adha sermons contribute significantly to enhancing the congregation's understanding of sincerity and sacrifice. Social activities such as the slaughter of sacrificial animals, meat distribution, communal cooperation mutual coopretion, and community service served as effective media for internalizing these values. Findings reveal that 88% of respondents experienced increased social awareness, and 84% demonstrated heightened empathy following their participation in the Eid al-Adha activities. Thus, Eid al-Adha sermons can serve as an effective Islamic guidance and counseling approach for shaping the religious and social character of the community.